Is a little pollution good for you? incorporating societal values in environmental research - Elliott, Kevin Christopher (New York ; Oxford : Oxford University Press, 2011)
Could low-level exposure to polluting chemicals be analogous to exercise - a beneficial source of stress that strengthens the body? Some scientists studying the phenomenon of hormesis claim that that this may be the case. This text critically examines the current evidence for hormesis.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 16, 2010).
Keywords: Environmental responsibility; Environmental ethics; Pollution